2015
DOI: 10.1016/j.ijom.2015.08.436
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of bioengineered bone in a muscle flap for reconstruction of a critical-size mandibular defect

Abstract: This study presents a comprehensive radiographic evaluation of bone regeneration within a pedicled muscle flap for the reconstruction of critical size mandibular defect. The surgical defect (20 mm615 mm) was created in the mandible of ten experimental rabbits. The masseter muscle was adapted to fill the surgical defect, a combination of calcium sulphate/ hydroxyapatite cement (CERAMENT TM |SPINE SUPPORT), BMP-7 and rabbit mesenchymal stromal cells (rMSCs) was injected inside the muscle tissue. Radiographic ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
5
1
1
Order By: Relevance
“…Our results suggest that preserving a muscular pedicle connected to the prefabricated scaffold can significantly enhance new bone formation. However, It has been consistent with Al‐Fotawei et al's study wherein they reconstructed a mandibular defect in rabbit by rotated flap of masseter muscle into which a commercial bone cement in the combination with BMP‐7 and MSCs was injected 11 . They radiographically demonstrated significant enhancement in bone regeneration of their design in comparison with the control site.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results suggest that preserving a muscular pedicle connected to the prefabricated scaffold can significantly enhance new bone formation. However, It has been consistent with Al‐Fotawei et al's study wherein they reconstructed a mandibular defect in rabbit by rotated flap of masseter muscle into which a commercial bone cement in the combination with BMP‐7 and MSCs was injected 11 . They radiographically demonstrated significant enhancement in bone regeneration of their design in comparison with the control site.…”
Section: Discussionsupporting
confidence: 79%
“…An alternative approach is to develop engineered tissues inside a living bioreactor, the body, while leveraging the self‐regenerative capacity of living body compartments. In vivo bioreactor (IVB) has been introduced as a new prefabrication technique for cell delivery in animals and human models 10–19 . The history of this method can be traced back to the 19th decade, when ectopic bone formation in muscles was reported with application of rhBMP2 12,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Plain X-ray was the most common choice for bone assessment in experimental and clinical research. 49 Our experiment adopted the average length of five referential lines as the alveolar ridge height at baseline within 2, 6, and 12 weeks after surgery, which reduced artificial interference factors due to the influence of different projection, body position. Through X-ray analysis, we found that the mean alveolar ridge height alteration in the 12th weeks of BG group was À1.73 mm, which was in line with the experimental results of À1.69 mm of Xue et al 50 suggesting that the measuring accuracy was sufficient to meet the requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Approval was obtained from the UK Home Office under the Animals (Scientific Procedures) Act 1986. Rabbit bone marrow aspiration, rMSCs isolation, culture, characterization and assessment of the cell-cement interaction followed a standard protocol 30 . The cement used in this study was injectable and commercially available (CERAMENT™lSPINE SUPPORT, Bone Support AB, Lund, Sweden) composed of 60% calcium sulphate, 40% hydroxyapatite powder and a liquid phase of water and an opacifier (Iohexol).…”
Section: Methodsmentioning
confidence: 99%
“…The mandibles were explanted and the surgical sites were examined. Samples were subjected to a comprehensive radiological evaluation 30 and then prepared for histological assessment.…”
Section: Surgical Proceduresmentioning
confidence: 99%